(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Charaspet K, Sukmasuang R, Khoewsree N, Pla-Ard M, Paansri P, Keawdee B, Chanachai Y, Bhumpakphan N. 2021. Spatial and temporal overlaps of top predators: Dhole, tiger and leopard, and their potential prey in Huai Kha Khaeng Wildlife Sanctuary, Thailand. Biodiversitas 22: 580-592. The study of the spatial-temporal overlap of top predators and their prey is important to understand competition among predators and predator-prey relationships so that the viable populations of predators and other animals can be sustained. This research aimed to study the abundance of three top predators: Dhole (Cuon alpinus), tiger (Panthera tigris) and leopard (Panthera pardus), and their potential wild prey in Huai Kha Khaeng Wildlife Sanctuary, Thailand, and to investigate the spatial-temporal overlap between those three predators, and their potential wild prey. We tested two significant hypotheses: (i) tiger and leopard had the highest spatial-temporal overlap and the spatial overlap of dhole and leopard was higher in comparison to dhole and tiger due to a higher prey overlap; (ii) the three species of large carnivore avoided spatial-temporal overlap even if they were in the same area. The study was conducted using camera traps. In addition, the spatial-temporal overlap of large carnivores and their potential prey was studied to understand the important species of prey of these large carnivores. The results showed that the spatial overlap of tiger and leopard was the highest. Dhole had significant spatial overlap with leopard, which was higher in comparison to dhole and tiger. A significant temporal overlap of dhole and leopard was not found. Also, a significant temporal overlap of tiger and leopard was not found. The results were based on hypotheses that conformed to the niche overlap index of the potential prey and the temporal overlap coefficient. There were ten important species of potential prey of large carnivores: Sambar deer (Rusa unicolor), red muntjac (Muntiacus muntjak), gaur (Bos gaurus), banteng (Bos javanicus), wild boar (Sus scrofa), Malayan porcupine (Hystrix brachyura), large Indian civet (Viverra zibetha), Asiatic black bear (Ursus thibetanus), pig-tailed macaque (Macaca nemestrina) and red jungle fowl (Gallus gallus). The important recommendation is the protection of the sanctuary from wildfires which spread from the outside in, especially in dry evergreen forest. Food resources of herbivores in the area must be managed, as well as the prevention of epidemics from livestock to wild animals.